Financing and developing the agricultural sector through cash waqf: an analysis of cash waqf using the mudarabah approach - Jaiyeoba, Haruna Babatunde; Nulambeh, Ndzembanteh Aboubakary; Ibrahim, Traore; Harun, Md Yousuf; Sanoh, Mory Fode (Zes Rokman Resources, 2015)
This research examines the viability of using cash waqf to develop the agricultural (poultry) sector based on a mudarabah approach. Collecting data for this research consisted of distributing questionnaires to 125 respondents in the International Islamic University Malaysia IIUM. Demographic and descriptive analyses (using Crosstabs) were used to analyse the collected data. The study found that the majority of respondents were aware of the meaning and use of cash waqf. According to the results, the majority of respondents support the incorporation of cash waqf into a mudarabah contract in order to provide employment opportunities for the needy. Furthermore, they support the use of cash waqf in the development of waqf land.